Penerapan Strategi Kewirausahaan dan Digital Marketing Pada UMKM Nasi Goreng Sarjana di Mangli Jember - Nufus, Shella Mauria Zakiatun; Fitriah, Mukarromatul; Aini, Alfinna Quratul; Kurniawati, Nilam Adelia; Maulinda, Lola Juwita; Aisyah, Siti; Budiarti, Nonik; M, Widah Hatin; Fateha, Amilia; Hasan , Misbahul; Muzayyin, Muzayyin (Journal of Health, Education, Economics, Science, and Technology, 2025)
This study aims to explore entrepreneurial strategies and the implementation of digital marketing in the Nasi Goreng Sarjana MSME located in Mangli, Jember. Using a descriptive qualitative approach, data were collected through observation and in-depth interviews with the business owner. The findings indicate that the entrepreneurial strategies employed include the utilization of personal assets, keen market observation, and business development through partnerships and branch expansion. On the other hand, digital marketing strategies are implemented through the use of social media platforms such as Instagram, TikTok, and WhatsApp, as well as collaborations with local influencers and digital food delivery services. These efforts are further supported by creative content and live streaming, which enhance consumer engagement and brand awareness. The use of unique menu names also serves as an additional attraction in building brand identity. The study reveals that the integration of experience-based entrepreneurship with adaptive digitalization can significantly improve the competitiveness of MSMEs in the digital economy era. This research provides valuable insights for the development of MSME business strategies, particularly in the culinary sector, and serves as an inspirational model for young entrepreneurs in Indonesia.